Efektivitas Edukasi Kesehatan Gigi Berbasis Video Animasi terhadap Keterampilan Menyikat Gigi pada Siswa SD Negeri 2 Carawali Kabupaten Sidenreng Rappang - Yulistina; Zainab; St. Nurbaya (Jurusan Keperawatan Gigi Poltekkes Kemenkes Makassar, 2025)
Dental and oral health is an integral part of overall health; however, it often receives less attention in school-age children. One of the most common problems is dental caries, which is closely related to poor tooth brushing skills. To address this issue, animated video media was applied as an interactive and enjoyable health education tool. This research aims to analyze the effect of dental and oral health education using animated video media on tooth brushing skills among grade I and II students at SD Negeri 2 Carawali, Sidenreng Rappang Regency. This study employed a quasi-experimental design with a pre-test–post-test control group. The research stages included preparation, intervention, and evaluation of tooth brushing skills. The results showed that animated video media was effective in improving children’s tooth brushing skills, with a significant increase in skill scores in the intervention group compared to the control group (p < 0.05). Thus, dental and oral health education using animated video media is feasible and effective in enhancing proper tooth brushing skills in early elementary school children.